HYBRID MODEL PROSPECTS FOR WAR CRIMES: NON-PARTY STATES TO THE ROME STATUTE (THE SRI LANKA CASE) - Arif Rohman (Kanun Jurnal Ilmu Hukum, 2023)
This article discusses the possibility of non-ratifying states to the Rome Statute to be refered to International Criminal Court (ICC) with reference to Sri Lanka, where war crimes and crimes against humanity has been occured. This study employed the doctrinal method to analyze the issue. Sri Lanka is unable to deal with perpetrators who must be responsible for humanitarian conflicts, despite of a sovereign State. This paper found that the United Nations has a responsibility in addressing war crimes and crimes against humanity in Sri Lanka when dealing with war crimes due to its non-ratification of the Rome Statute. Sri Lanka can propose the formation of an Ad Hoc Tribunal to the United Nations, adopting a judge composition inspired by hybrid models used in Sierra Leone and Cambodia. However, the legality of foreign judges must be clarified beforehand.